Diagnosis and treatment of Aspergillus terreus and Klebsiella pneumoniae coinfection following myocardial infarction: A case report and literature review - Hang Yu; Zhi-Kun Luo; Ting-Ting Lu; Yue Deng; Jia-Ni Xia; Wan-Yue Li; Jing-Hao Li (IDCases, 2025)
Background: Aspergillus terreus (A. terreus) is an opportunistic fungal pathogen increasingly reported among immunocompromised individuals, particularly those admitted to intensive care units (ICUs). Due to its intrinsic resistance to amphotericin B and partial resistance to azoles, treatment remains challenging. Coinfection with bacterial (Klebsiella pneumoniae [K. pneumoniae]) and viral pathogens (herpes simplex virus type 1 [HSV-1], cytomegalovirus [CMV]) further complicates the clinical course. Case report: We describe a 53-year-old male who developed A. terreus and K. pneumoniae bloodstream infections following acute myocardial infarction (MI). Diagnosis was primarily achieved via next-generation sequencing (NGS) of blood samples, supplemented by clinical and imaging findings. Despite aggressive antimicrobial therapy—including isavuconazole, liposomal amphotericin B, piperacillin-tazobactam, and mechanical support strategies (e.g., extracorporeal membrane oxygenation [ECMO], continuous renal replacement therapy [CRRT])—infection control was difficult. The patient eventually recovered partial consciousness and was discharged for rehabilitation. Discussion: Invasive fungal infections, particularly those caused by A. terreus, present diagnostic and therapeutic challenges in critically ill patients. Early molecular identification and tailored antifungal therapy based on pathogen resistance profiles are essential. Moreover, recognizing and managing bacterial and viral coinfections are vital for optimizing patient outcomes. Conclusion: This case highlights the necessity of prompt, multimodal diagnostic approaches and individualized antifungal and antibacterial therapy in the management of ICU-acquired infections post-myocardial infarction.